Management of pencak silat sports facilities and infrastructure padepokan IPSI Jepara Regency in 2022 - Wahyu Indra Wijaya; Limpad Nurrachmad (Universitas Sriwijaya, 2023)
Facilities and infrastructure are one of the indicators and factors for achieving successful sports achievements, especially martial arts. This study aims to describe the implementation of the management of martial arts sports facilities and infrastructure in the IPSI padepokan of Jepara Regency along with the obstacles faced and the response of users of the Jepara Regency IPSI padepokan.This research is a qualitative research with a descriptive approach. The research location was carried out in padepokan IPSI Jepara Regency with the subject of the study, namely the administrators, coaches and martial arts athletes of Jepara Regency. The data collection methods used include observation, interviews and documentation. The data analysis techniques used in this study are data validity, data reduction, data presentation, and drawing conclusions or verification.The results showed that the management pattern of infrastructure of Padepokan IPSI Jepara Regency consists of planning, procurement, storage, inventory, maintenance, removal and supervision. The management of infrastructure is determined for the implementation of sports activity programs and sports equipment used during training and competition. The challenges faced are the implementation of the work program properly and the maintenance of sports infrastructure in the padepokan. Meanwhile, the obstacle is human resources seen from the aspects of the work environment, organizational culture and other parties or outsiders. The response was both expressed by athletes and coaches as users of the Jepara Regency IPSI padepokan. It can be seen that there is an increase in motivation to train and compete in championships from the application of sports infrastructure management and athletes when training feel comfortable and proud of the availability of existing facilities